City CarShare: Assessment of Intermediate-Term Travel-Behavior Impacts - Robert Cervero; Nina Creedman; Muhammad Pohan; Madhav Pai; Yu-Hsin Tsai (University of California, Institute of Urban and Regional Development (IURD), 2002)
Some nine months into the introduction of car-sharing in the City of San Francisco, an estimated 7 percent of members' trips were by City CarShare vehicles, up from around 2 percent just six months earlier. At the nine-month mark, more than 20 percent of members' vehicle miles traveled (VMT) was by car-share vehicles, a substantial jump from what it was earlier. Evidence suggests that access to car-share vehicles is stimulating motorized travel. Most members do not own cars and many appear to be leasing vehicles in lieu of walking and biking. Car-share vehicles are used more for personal business and social-recreational travel than non-discretionary, routine travel such as to work or school. Cars generally are not used frequently during peak periods or to dense settings well-served by transit, like downtown. In this sense, car-sharing appears to be stimulating a resourceful form of "automobility." Users are accruing substantial travel-time savings, and willingly pay market prices for these benefits. Survey results also suggest that car-sharing is cutting into private car usage, especially among higher income members. This appears to be less because members are getting rid of cars and more due to them selectively substituting City CarShare vehicles for their own. Predictive models revealed that the likelihood of car-share usage increased with members' personal incomes, educational levels, and age. Also, members were more likely to lease vehicles if they lived in zero-car households.
Keywords: 330